2007
DOI: 10.1523/jneurosci.3772-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Serotonin and Dopamine on Human 5-HT3AReceptor Kinetics: Interpretation within an Allosteric Kinetic Model

Abstract: Serotonin type 3 (5-HT 3 ) receptors are members of the pentameric Cys-loop superfamily of receptors that modulate synaptic neurotransmission. In response to agonist binding and unbinding, members of this superfamily undergo a series of conformational transitions that define their functional properties. In this study, we report the results of electrophysiological studies using rapid solution exchange designed to characterize and compare the actions of the high-efficacy agonist serotonin and the low-efficacy ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 40 publications
13
54
0
Order By: Relevance
“…A recent study by Solt et al (2007) indicates that desensitization produced by 5-HT dominates the channel closure process even following agonist removal (i.e. our "deactivation" paradigm).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…A recent study by Solt et al (2007) indicates that desensitization produced by 5-HT dominates the channel closure process even following agonist removal (i.e. our "deactivation" paradigm).…”
Section: Discussionmentioning
confidence: 94%
“…We performed kinetic simulations of receptor function designed to look at current decay in the continuous presence of 30 μM 5-HT and after agonist removal (Figure 10) to determine if our findings with 5-HI could be completely explained by reduced desensitization rate. We used the allosteric model developed by Solt et al (2007) and the kinetic parameters shown in Table 2. Indeed, we could produce reasonable simulations of the 5-HI-induced prolongation of current decay under either continuous or transient agonist application conditions by decreasing the forward desensitization rate constant (K d+ ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macroscopic dose-response and single-channel kinetic analyses of homomeric Cys-loop receptors suggest that two to five agonist molecules are required for maximal activation (Amin and Weiss, 1996;Palma et al, 1996;Papke et al, 2000;Mott et al, 2001;Gentet and Clements, 2002;Beato et al, 2002Beato et al, , 2004Solt et al, 2007). However, because dose-response and single-channel measurements cannot directly reveal the number and locations of functional binding sites, this remains a crucial gap in our mechanistic understanding of homomeric Cys-loop receptors.…”
Section: Introductionmentioning
confidence: 99%